Tackling Sustainable Development Goals in Italian Regional Legislation: a Health in All Policies comparative analysis. (30th September 2020) - Stirparo, G; Rallo, F; Gori, D; Blandi, L; Seidenari, C; Bizzarro, A; Gaetti, G; Rossi, D; Odone, A; Signorelli, C
Abstract: Background: The Health in All Policies approach has been increasingly used to assess public health impact of rules and regulations. In 2015, all UN member States adopted 17 Sustainable Development Goals (SGDs) to achieve the 2030 Global Agenda. SDGs can be conceived in a practical way, as analytic tools to classify existing legislation. In the context of the ASPHER-ASPPH sponsored "This is Public Health in Italy" campaign, the Public Health Schools of University San Raffaele, University of Bologna, University of Pavia and University of Parma decided to monitor their own local governments' level of SDG compliance. The study aims at identifying a procotol for a Health in All Policies, SDG-driven analysis in two Northern Italy Regions: Lombardy and Emilia-Romagna. These two regions 4.45 millions and 10.04 million accounting for over 24% of national population. Methods: Between November and December 2019, two teams were established for separate analyses of the 2 Regions. All laws were retrieved from the two Regional Council's offical websites. Exclusion criteria were set by ruling all healthcare-related laws out of the analysis. An agreement was reached to label each law with the most representatives SDG tackled. As a proxy for internal validity, results were double-blinded. Each Regional Group met collectively and double-checked the other group's anlysis. To minimise detection bias, results were sent anonymously to the Scientific Committee, who supervised the analytic process and solved disagreements. Results: A total of 57 laws were examined, 26 issued by Lombardy Region and 31 by Emilia-Romagna Region. SDG-related laws number was: 11 (42%) in Lombardy Region, whereas in Emilia-Romagna Region the proportion was much higher (n = 22, 71%). The most addressed SGD in Lombardy Region was number 15 (Life on Land), while in Emilia-Romagna number 8 (Decent Work & Economic Growth). Conclusions: SDGs can be considered an innovative indicator to measure governement's activities and monitor the progress towards achieving the 2030 Global Agenda. Key messages: Sustainable Development Goals are useful tools for policy analysis. The "This is Public Health in Italy" campaign allowed for a survey of public health legislative initiatives.